Information systems evaluation in context – impact of the corporate level - Piotrowicz, W; Irani, Z (2008)
The paper presents the results of a doctoral research related to Information Systems evaluation in context. The authors propose changes in the context, the new level of contextual analysis was added: the system context located between the internal and external context. The system context reflects the fact that the case companies are business units and parts of the corporations and IS evaluation is influenced by the corporation, Three levels of context analysis can be used in case of IS evaluation in complex structures, such as corporations or supply chain.